(untitled) (Revista Innova Educación, 2020)
Companies focus on eco sustainability and their contribution to sustainability is aimed at rethinking new practices for ecological products and waste disposal, committed to the environment. Objective: To describe and interpret the management of ecofriendly practices in supermarkets, based on the perception of university students and managers, to contribute towards a model of responsible culture management with the environment in organizations. Method: Qualitative-quantitative, mixed approach, non-experimental design, descriptive and interpretive type. It shows 93 university students and 02 managers, a cross-sectional survey and in-depth interviews. Results: The management of ecofriendly practices in supermarkets is comprehensively rated as regular with 37% according to the perception of university students; the management of waste energy and water qualifies regular with 30%, requires attention as centers of new income and reduction of expenses. Conclusion: The construction of the empirical bases of the ecofriendly management model are: Products, packaging and eco-labels. Waste, energy and water. Environmental communication and infrastructure.